Emissions of nitrous oxide associated with frost killed cover crops - Olofsson, Felicia (2022)
Agriculture is responsible for approximately 80% of anthropogenic emissions of the potent and long-lived greenhouse gas nitrous oxide (N2O). N2O emissions from agricultural soils are characterized by high temporal and spatial variability and often peak in short bursts related to events such as precipitation, fertilization and soil thawing. Frost-sensitive cover crops (CCs) could potentially enhance N2O emissions during winter. This thesis work investigated the thaw-related N2O fluxes induced by three different cover crops (oilseed radish, (Raphanus sativus), phacelia (Phacelia tanacetifolia) and oats (Avena sativa)) by field measurements during a six-week winter period when the CCs were successively terminated by low temperatures. It was hypothesized that the magnitude of the emissions would be related to the content of nitrogen (N) and soluble carbon (C) components in the CC aboveground biomass, as these are substrates for denitrifying soil bacteria. Results showed that oilseed radish plots had the highest cumulative emissions of N2O during the study period, at 3.3 kg ha-1, whereas phacelia and oat plots each emitted 1.4 kg ha-1, all significantly higher compared to control plots without CCs. The content of N and soluble C components in aboveground biomass could not fully explain the emissions of N2O. However, it is possible that belowground biomass was important, or that other qualities of the biomass were influential in governing thaw-related N2O flux.